(3GdeKdKs - (3YHO Gddg Hf eMeO Hf GdSjO GdHWdjhSj, GHf GdSjO GdHWdjhSj, CHh eMeO J (B521 (3g` s
(3ChdgG (B:s
(3HGH GdeKdK GdeJab GdeYGfi , hgj KdGK YTQI cdeI s
(3BNQgG (B:s
(3CKfGA MQa GdjGA GdeKdK GdeJab GdeYGfi , Hbhdg (B: (3hgh jgQ HGdVe dGZjQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B199 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs